Archaeological networks and social interaction - Donnellan, Lieve (Routledge studies in archaeology, 2020)
"Archaeological Networks and Social Interaction focuses on conceptualisations of human interaction, human-thing entanglement, material affordances and agency. Network concepts in the archaeological discipline are ubiquitous these days. They range from loose concepts, used as metaphors to address a notion of connectivity, to highly formal and mathematically complex predictions of human behavior. These different networked worlds sometimes clash and rarely converge. Archaeologists interested in network analysis, however, have achieved a much better understanding of the implications of adopting formal methods for studying social interaction and there have been theoretical advancements realizing a better synergy between different theoretical perspectives. These nascent concerns are explored further in this volume with regional specialists exploring case studies from Prehistory to the Middle Ages throughout the Ancient and New Worlds, outlining how formal network approaches contribute to studying social interaction archaeologically. This book will be of interest to archaeologists wishing to access the latest research on networks and interconnectivity and how these approaches have been productively modified to archaeological research"--